Assessing the Impact of Asset Management on Energy Recovery: The ENERGIDRICA Project - Andres Ariza; Laura Enriquez; Antonietta Simone; Francesco G. Ciliberti; Daniele B. Laucelli; Luigi Berardi (Engineering Proceedings)
The ENERGIDRICA project was born in 2017 at a time of transformation in the “management of water infrastructure” in Italy due to socioeconomic and technological events that have determined the current operational context, in which the “digital transition” represents an opportunity to make the processes related to the management and planning activities for these systems more effective and efficient. The concept of the water–energy nexus is the basis of ENERGIDRICA because an efficient use of energy in aqueducts has positive hydraulic and CO2-related impacts.